Análisis comparativo entre la metodología de diseño basada en fuerzas y la metodología de diseño basada en desplazamientos para sistemas combinados (2015)
This article presents the results of a comparative analysis between the force-based design methodology and the displacement-based design methodology. Three reinforced concrete structural system structures were modeled. The differences between both methodologies and the advantages of using the displacement-based design methodology were established in that they allow a better understanding of the design process and obtain consistent overall displacement and stiffness values of the structure, in comparison with those obtained in a verification process by means of a static nonlinear analysis.